The achievement of water management objectives based on willingness to pay for a water service fee in tidal lowlands - Yazid, Muhammad; Shamsudin, Mad Nasir; Abdul Rahim, Khalid; Radam, Alias; Muda, Azizi (Taylor and Francis, 2013)
The objective of this study was to estimate willingness to pay for a water service fee (WSF) in order to assess the expected achievement of water management objectives in tidal lowlands. A survey was conducted in Telang, a tidal lowland area on the eastern coast of Sumatra, involving 500 water users randomly drawn from approximately 60,000 people living in the delta. Each respondent was interviewed to obtain information regarding socioeconomic status and the willingness to pay for WSF. The data were analyzed using multiple regresion to obtain the estimate of WSF and its affecting factors. Results indicated that the mean WSF was $11.40 US. With this WSF, only the improvement of water distribution objectives could expect to be achieved.